The Learning Curves for Laser Application in Urology Procedures: Review of the Literature: Learning Curves for Urological Lasers - Allameh, Farzad; Razzaghi, Mohammadreza; Abedi, Amir Reza; Dadpour, Mehdi (Journal of Lasers in Medical Sciences, 2020)
Introduction: Currently, a laser is a popular technology in urological surgeries. The important laser-related issue is the time when a surgeon reaches an acceptable level of safety and efficacy using laser technology. Methods: In this review, we aimed to assess the learning curves of three types of surgeries in urology, including photoselective vaporization of the prostate (PVP), holmium laser enucleation of the prostate (HoLEP), and retrograde intra-renal surgeries (RIRSs). Here, we searched Medline, Web of Science, Google Scholar, EMBASE, and Scopus for such keywords as Urology, laser, laser vaporization, prostate, nephrolithiasis, benign prostatic hyperplasia (BPH), and learning curve. Results: We evaluated 14 studies about PVP, 17 about RIRS, and 29 studies about HoLEP. Also, we separately discussed the learning curves of these three kinds of surgeries in detail. Conclusion: All the urologists, even expert surgeons, should attend a formal training course and have a skilled tutor present in their first cases.